Identification of Agroforestry Systems and Socio-Economic Status of Farmers in Rural Areas of Jogindernagar in Mandi District of Himachal Pradesh, India - , Som Dutt Sharma, Ananya Sharma, Ravindra Kumar Dhaka, Navjot Singh Kaler, Naresh Thakur (Archives of Current Research International, 2024)
The present study was carried out in rural areas of Jogindernagar in Mandi District of Himachal Pradesh with the aim of identifying the agroforestry systems and assessing the demographic features and socio-economic status of farmers. The methodology followed for the present study in order to site selection, sampling procedure, identification of agroforestry systems, data collection, an analytical framework and valuation. The study site was selected by multistage random sampling technique. The study revealed that there are six agroforestry systems viz., agrisilviculture, agri-silvi-horticulture, agri-horticulture, agri-silvipastoral, pastoral-silviculture and pastoral-horticulture which prevails among different categories of farmers. In the medium and small categories of farmers, all the six agroforestry systems were present, while in the marginal category of farmers, the agri-silvipastoral system was absent. The average family size of the sampled households was 5.59 individuals per family. The highest sex ratio was observed in marginal farmers (990) and the lowest in medium farmer category (834). The literacy rate was recorded at its highest (91.70) in the marginal category of farmers. Most of the women were employed in the agroforestry and their livelihood depends on the farm’s income. The highest percentage of local breeds of cows was found in the all three categories of farmers. Overall, average land holding was recorded at 3.07 hectares in all sampled categories of farmers. The average land holding area was found to be maximum (1.58 ha) in medium, followed by small (1.01 ha) and marginal (0.48 ha) categories. Thus, small scale agroforestry viz., Agri-silvi-horticulture system in the subtropical region of Himachal Pradesh is recommended for social, economical and environmental benefits to the rural population for their livelihood and food security in the climate change era.